A study of atom and radical kinetics - Hanning-Lee, M; Mark Hanning-Lee (1990)
This thesis describes the measurement of rate constants for gas phase reactions as a function of temperature (285 ≤ T/K ≤ 850) and pressure (48 ≤ P/Torr ≤ 700). One or both reactants was monitored directly in real time, using time–resolved resonance fluorescence (for atoms) and u.v. absorption (for radicals). Reactants were produced by exciplex laser flash photolysis. The technique was used to measure rate constants to high precision for the following reactions under the stated conditions: • H+O2+He->HO2+He and H+O2−→OH+O, for 800 ≤ T/K ≤ 850 and 100 ≤ P/Torr ≤ 259. A time–resolved study was performed at conditions close to criticality in the H2–O2 system. The competition between the two reactions affected the behaviour of the system after photolysis, and the rate constants were inferred from this behaviour. • H+C2H4+He<-->C2H5+He (T = 800 K, 97 ≤ P/Torr ≤ 600). The reactions were well into the fall–off region at all conditions studied. At 800 K, the system was studied under equilibrating conditions. The study provided values of the forward and reverse rate constants at high temperatures and enabled a test of a new theory of reversible unimolecular reactions. The controversial standard enthalpy of formation of ethyl, DH0f,298 (C2H5), was determined to be 120.2±0.8 kJ mol−1. Master Equation calculations showed that reversible and irreversible treatments of an equilibrating system should yield the same value for both thermal rate constants. • H+C3H5+He->C3H6+He (T = 291 K, 98 ≤ P/Torr ≤ 600) and O+C3H5 −→ products (286 ≤ T/K ≤ 500, 48 ≤ P/Torr ≤ 348). Both reactions were pressure–independent, and the latter was also independent of temperature with a value of (2.0±0.2) ×10−10 cm3 molecule−1 s−1. • H+C2H2+He<-->C2H3+He (298 ≤ T/K ≤ 845, 50 ≤ P/Torr ≤ 600). At 845 K, both reactions were in the fall–off region; rate constants were used to determine the standard enthalpy of formation of vinyl, ¢H0f,298 (C2H3), as 293±7 kJ mol−1. The value of this quantity has until recently been very controversial. • H+CH4 <--> CH3+H2. The standard enthalpy of formation of methyl, DH0 f,298 (CH3), was determined by re–analysing existing kinetic data at T = 825 K and 875 K. A value of 144.7±1.1 kJ mol−1 was determined. Preliminary models were examined to describe the loss of reactants from the observation region by diffusion and pump–out. Such models, including diffusion and drift, should prove useful in describing the loss of reactive species in many slow–flow systems, enabling more accurate rate constants to be determined.